Classroom based performance-feedback influencing advanced English I students´ speaking skill in the target Language at the Foreign Language Department of the University of El Salvador - Flamenco Flamenco, Juan Antonio; Pichinte Ardon, Oscar Dalton (2024)
The research was carried out to provide a relationship between Classroom Based Performance feedback and the influence on students’ speaking skill in the Target Language at the Advanced Intensive English I courses at the Foreign Language Department of the University of El Salvador. The study showed a correlation between Classroom-based performance feedback and students´ speaking proficiency in the Target Language. This research demonstrated the correlation among the two variables mentioned before. Competence Based Performance is a new tendency for teaching a foreign language that emerged in the United States in the 1970s. This new tendency was well accepted and adapted in the United States Educational System as well as this type of teaching was based on what English as Foreign Language (EFL) students could do with the Target Language inside the classroom and they could demonstrate that they were able to do applying the knowledge that they have studied in the class by performing a task in the Target Language (Nunan, 1999). As it is stated in the findings of the present study, there is a strong correlation between Classroom based performance-feedback and students´ speaking proficiency when using the Target Language. The study showed that when professors from Advanced Intensive English I courses at the Foreign Language Department used oral activities (Oral presentations, Dialogues, Role plays, Debates and class discussion) to practice in the classroom, students demonstrated a higher proficiency in their Speaking ability. The main objective of this research was to find out the correlation between classroom based performance feedback and the proficiency that students demonstrated when speaking at the Advanced Intensive English I courses at the Foreign Language Department at the University of El Salvador. By considering this main objective, researchers provided scientific data that could demonstrate the correlation between Classroom Based Performance- Feedback and students´ speaking skill stating the correlation between the two variables. The first specific objective developed by the researchers was to find out what types of classroom based performance feedback were used to promote students’ speaking skill in the Advanced Intensive I courses at the Foreign Language Department at the University of El Salvador. Finally, the last objective was to describe the standards that students from Advanced Intensive I courses from the University of El Salvador are supposed to be reaching in this course. In order to find out the correlation between the two variables stated before; it was necessary to follow some steps. Researchers narrowed the topic down from ‘’ Classroom based performance and students´ speaking skill into Classroom based performance-feedback and students´ speaking skill. Then, researchers had to find out the appropriate literature review to answer the research question that was ‘’How does classroom based performance-feedback influence Advanced Intensive English I students’ speaking skill in the target language at the Foreign Language Department of the University of El Salvador?’’ After reading the literature review, the scholars wrote the statement of the problem and how to approach it. Besides that, the researchers created a survey about classroom based performance activities that were developed in the classroom. Furthermore, researchers piloted the survey to find out if the instrument was practical and reliable. The students that helped researchers out to pilot the survey were twenty students. Researchers made some changes to the survey due to the fact that some students got confused at the moment of completing it. After administering one more time the survey with the appropriate changes, scholars were able to determine which classroom based activities were used in the classroom to increase students’ speaking in the target language. According to the results gotten in the survey, researchers were able to determine that if teachers use Classroom based performance-feedback activities students will develop a higher proficiency when speaking. The most common oral activities used by students from Advanced Intensive I courses were oral presentations, dialogues, role plays, debates, and class discussion. Moreover, researchers concluded that there was a strong correlation between Classroom based performance-feedback and students´ speaking skill in the Target Language since they were able to prove that when teachers use classroom-based performance activities students were able to develop a higher proficiency when speaking.